Economic Empowerment of Small Businesses Through Zakat Funds at the Amil Zakat Infaq Shadaqah Institute in Surakarta - R Rahmat (Walidem Institute and Publishing (WIP), 2024)
The purpose of this study is to determine the management and economic empowerment of small business communities and the form of empowerment carried out by the two LazisMu. This type of research belongs to the category of field research with a qualitative research approach. Data sources were obtained through observation, interviews, and documentation. Data analysis techniques are reducing data, presenting data, and drawing conclusions. The results of the research include: The collected zakat funds are given to the poor who can do entrepreneurship on the recommendation of the Muhammadiyah Business Leadership or Charity. Management and economic empowerment of small business communities, LazisMu distributes zakat funds directly to individuals and through institutions after an investigation by LazisMu, Zakat funds given can be empowered in various programs that can improve the welfare of the Ummah as currently done by LazisMu is given in the form of business capital. Among them are LazisMu UMS through the By Friend and By Requets programs including business capital, assisted villages, entrepreneurship training, and mentoring marginalized people to mustahiq while LazisMu PDM Surakarta City through the Economic Empowerment Program including Aisyiyah Family Economic Development (Bu-Eka) and business carts. LazisMu UMS has distributed its productive zakat funds, including providing goods or equipment assistance to mustahiq/people who support their entrepreneurial fields, while LazisMu PDM Surakarta City also provides in the form of creative productive in the form of financial assistance or equipment in the field of entrepreneurship.